2020
DOI: 10.1111/ajt.15753
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the microbiota for therapeutic purposes

Abstract: The myriads of microorganisms colonizing the human host (microbiome) affect virtually every aspect of its physiology in health and disease. The past decade witnessed unprecedented advances in microbiome research. The field rapidly transitioned from descriptive studies to deep mechanistic insights into host‐microbiome interactions. This offers the opportunity for microbiome‐targeted therapeutic manipulation. Currently, several strategies of microbiome‐targeted interventions are intensively explored. Best eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The dynamics of microbial strains in engraftment processes and species interdependency add another compounding level of factors that are relevant to FMT efficacy. Understanding the diversity and variability of individual microbiome differences is of vital importance in FMT [ 132 ].…”
Section: Future Perspectives Of Fmt In Human Medicinementioning
confidence: 99%
“…The dynamics of microbial strains in engraftment processes and species interdependency add another compounding level of factors that are relevant to FMT efficacy. Understanding the diversity and variability of individual microbiome differences is of vital importance in FMT [ 132 ].…”
Section: Future Perspectives Of Fmt In Human Medicinementioning
confidence: 99%
“…Due to recent discoveries, it is now clear that gut microbiota is very responsive to the influence of probiotics, regulating general health and organic disorders, including CVDs, especially atherosclerosis and its acute consequences (coronary heart disease and stroke) ( 9 ) and hypertension ( 26 ). Some studies have shown that probiotics can modify the levels of metabolites, DNA, and components of the immune system, can activate immune cells, stimulate the production of immunoglobulins and regulate cytokines, demonstrating anti-inflammatory and immune effects in the host ( 134 , 136 ). However, the connection between probiotics, miRNA, gut microbiota and organic diseases is still not well known, being a relatively novel field of research that needs further investigations.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Probiotics may affect the immune system by changing the levels of metabolites, components, and DNA. They have been shown to activate immune cells, increase the production of immunoglobulins, and regulate cytokines (Khoruts, 2018;Sanders et al, 2019;Liwinski and Elinav, 2020;Yan and Polk, 2020). Several studies have demonstrated that these probioticderived factors can suppress intestinal inflammation via targeting toll-like receptor (TLR) signaling (Gómez-Llorente et al, 2010).…”
Section: Probiotics and Their Implications For Host-microbe Interactionsmentioning
confidence: 99%